Methodological Aspects of Environmental Labour Market Analysis - Jürgen Blazejczak; Dietmar Edler (Deutsches Institut für Wirtschaftsforschung (DIW), 1997)
High and persistent unemployment rates and increasing awareness of environmental degradation in many industrial countries have promoted the interest in the labour market effects of environmental policy. Environmental labour market analysis is fraught with many difficulties, however. Being unaware of these problems may result in misunderstandings and mislead policy makers. In environmental labour market analysis two kinds of questions have to be distinguished: firstly, accounting for the number of persons working directly or indirectly for environmental protection activities and secondly, identifying the net effect of environmental policy on the labour market balance. Answering the first question is not conceptionally contentious. However, elaborating quantitative estimates poses a variety of problems of delimitation and data collection which are discussed in some detail in section 2. This section also presents the results of studies assessing environmental employment in Germany in various dimensions. Section 3 deals with problems arising when one attempts to answer the question of how many additional jobs are created through environmental policies. This requires an assessment of secondary economic effects of environmental policy the size and even the direction of which depend on a variety of framework conditions in a complex way. Quantitative estimates can only be based on model simulations; thus the features of the models applied become crucial for the results. Some rules for making such estimates are discussed. The most important mechanisms to be taken into account are presented. Some examples of empirical studies for Germany are presented in order to illustrate the argument. The most important conclusion we draw is that the delimitations, methods and assumptions underlying any estimates of the labour market effects of environmental policy have to be clearly stated.
Keywords: 330; Umweltschutz; Beschäftigungseffekt; Statistische Methode; Bundesrepublik Deutschland